Measuring the Proficiency of Physical Education Teachers in Utilizing Information and Communication Technology for Virtual Classes - Nazemi Bidgoli, Alireza; Mahmoudi, Ahmad (AI and Tech in Behavioral and Social Sciences, 2025)
Technology is advancing at an astonishing pace, and this wave of innovations has opened a new window to the world of education. In this world, online classes have replaced the conventional classroom setting, eliminating concerns such as exorbitant costs, time-consuming transportation, and environmental challenges. As a result, virtual education has become a desirable option. Based on this, the aim of this research was to assess the proficiency of physical education teachers in utilizing information and communication technology in virtual classes. The current research employs a descriptive quantitative approach. The statistical population of the research included full-time faculty members and visiting professors from the sports science faculties of Tehran universities (Tehran, Kharazmi, Al-Zahra, Shahid Beheshti, and Allameh Tabatabai universities). A statistical sample of 97 individuals was selected based on Morgan’s table. To collect research data, a researcher-designed questionnaire was utilized. The questionnaire was prepared by utilizing library resources and was constructed around a five-point Likert scale. The content validity of the questionnaire was verified by 10 university professors. Additionally, the questionnaire’s reliability was determined through the calculation of Cronbach’s alpha coefficient, which yielded a value of 0.93. The research results indicate that enhancing the information technology abilities of physical education professors can greatly support both in-person and online education. It is recommended that heads of faculties and faculty members take the initiative in adopting and utilizing this technology across different educational contexts, considering its ongoing advancements.